The effect of alkali treated pineapple fibre on the properties of plasticized polylactic acid/epoxy palm oil blend - Mohamad, Nur Lisa Farhana; Awale, Raina Jama; Ali, Fathilah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Natural fibers are low cost, renewable, and environmentally friendly, and are suitable to be used as reinforcing agent to improve the properties of biopolymers. In this study, polylactic acid (PLA) based bioplastic composites reinforced with treated pineapple fibers (PALFs) and plasticized with epoxy palm oil were fabricated using melt blending method. Important parameter for surface treatment of fiber is the concentration of alkali used where it will disrupt the surface of the fiber and then functionalize it. Therefore, PALFs were alkali treated with 10%, 15%, and 20% potassium hydroxide (KOH) for 24 hours to improve the interaction between the fiber and PLA matrix. The composites were characterized using universal tensile test to evaluate the impact of alkali treatment on the mechanical properties on PLA/EPO/PALF blend, followed by differential screening calorimetry (DSC) test, and scanning electron microscopy (SEM) to observe the surface morphology of the composites. The composite with 15% KOH treated PALF was found to possess the highest stress, while the composite with 10% KOH treated PALF possessed the highest elongation-at-break which were obtained from the tensile properties. Incorporation of fibers into plasticized PLA further reduced the glass transition temperature which indicated increased chain mobility. Whereas, surface morphologies for tensile failed samples of treated fibers composites showed exfoliated fiber structures compared to the untreated fibers. These plasticized PLA/fiber composites treated with alkali showed enhanced properties compared to the untreated, in which, it showed the high potential of these composites to be used for environmental friendly packaging materials.